2014
DOI: 10.1093/bja/aeu240
|View full text |Cite
|
Sign up to set email alerts
|

Short-term changes of intraocular pressure after cervical interlaminar epidural injection: a pilot study

Abstract: CEI resulted in an elevation of IOP of both eyes. However, the effects were transient only lasting a few minutes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…7 Kang et al found that the IOP started increasing after the insertion of the Tuohy during a neuraxial intervention and continued to increase for 2 min after the intervention. 8 It was commonly reported in various studies and reviews that sudden IOP spikes could be observed due to the increased CSF pressure observed in neuraxial interventions. It has been reported that increased translamina cribrosa pressure could be of critical importance in patients who were at risk of loss of vision.…”
Section: Discussionmentioning
confidence: 98%
“…7 Kang et al found that the IOP started increasing after the insertion of the Tuohy during a neuraxial intervention and continued to increase for 2 min after the intervention. 8 It was commonly reported in various studies and reviews that sudden IOP spikes could be observed due to the increased CSF pressure observed in neuraxial interventions. It has been reported that increased translamina cribrosa pressure could be of critical importance in patients who were at risk of loss of vision.…”
Section: Discussionmentioning
confidence: 98%